2009
DOI: 10.1016/j.jjcc.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic function is abnormal in diastolic heart failure: Re-assessment of systolic function using cardiac time interval analysis

Abstract: Our results revealed that the major differences between ADD and DHF were global and longitudinal LV systolic dysfunction and LV enlargement. This study suggests that LV systolic dysfunction plays an important role in the development of DHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…24 Posterior wall thickness (PWT), interventricular septal thickness (IVS), left ventricular systolic (LVDs) and diastolic (LVDd) dimensions were determined. Left ventricular (LV) mass was calculated by the ASE-recommended formula: 25…”
Section: Evaluation Of Outcomesmentioning
confidence: 99%
“…24 Posterior wall thickness (PWT), interventricular septal thickness (IVS), left ventricular systolic (LVDs) and diastolic (LVDd) dimensions were determined. Left ventricular (LV) mass was calculated by the ASE-recommended formula: 25…”
Section: Evaluation Of Outcomesmentioning
confidence: 99%
“…On the other hand, HT is a common cause of diastolic and systolic heart failure, and some studies have reported that these disorders can be present in same patient. [28,29] LVEF and mitral inflow velocities are commonly used to evaluate global LV systolic and diastolic functions, respectively. However, measurement of LVEF has a number of well-known limitations.…”
Section: Discussionmentioning
confidence: 99%
“…One possible future direction of study for our system is utilizing its unique ability to vary the timings between electrical and mechanical stimulation to mimic the change of isovolumic contraction time (ICT) that occurs in normal development [40][41][42] or to model various myocardial diseases, 13,[43][44][45] specifically those that affect the ICT. For example, in fetal heart development, four different distinct stages of development occur, each with its own contraction mechanics and conduction parameters.…”
Section: Future Directions In Modeling Development and Diseasementioning
confidence: 99%
“…51 When increases in afterload occur through reductions in the wall shortening and stroke volume, it leads to decreased performance, ultimately causing heart failure. Another potential example where the ability to alter the timing between electrical and mechanical stimulation could offer greater insight into the disease process involves patients with LV myocardial disease, where the ICT is increased significantly, from 35 § 26 ms to 69 § 30 ms, 44 likely due to decreased myocardial contractility. 52 In patients with heart failure, the widening of the QRS complex indicates an impaired or slowed propagation of the electrical input, which is associated with increased morbidity and mortality.…”
Section: Future Directions In Modeling Development and Diseasementioning
confidence: 99%